If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 19 = 4 Reorder the terms: 19 + -4y = 4 Solving 19 + -4y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -4y = 4 + -19 Combine like terms: 19 + -19 = 0 0 + -4y = 4 + -19 -4y = 4 + -19 Combine like terms: 4 + -19 = -15 -4y = -15 Divide each side by '-4'. y = 3.75 Simplifying y = 3.75
| x^2-176=0 | | 2(6d+2)=18-3(16-3d) | | (5-c)/3=(2c+2)/(-4) | | -4m^2-4m+3=0 | | 5(9-z)+3=23 | | 9(2+w)-4w=3w+10 | | 4(1+x)=b-a+2x | | -x-4=3 | | 0.25c-6=2 | | x-1+5x=25 | | 700+35=450x(15) | | 2(3x-2)+x=8+x | | 5x-4(x-18)=84 | | 40=-2(22-x)+4(x-3) | | 4+7y-3=22 | | 6x-(-3x)+x-6= | | 3k+5(k-10)=10 | | 9(2+w)-4=3w+10 | | 5abc+4+l=13+f | | 4x^2+26+30=0 | | 4(x+2)+x+1=2x-3+3(x+4) | | 2-3x-4=2x-9 | | p-7=29 | | -8y-2y-4+4y= | | 3x^2+8x-19=x^2+1 | | 3(x+7)=-27 | | 15=7x-6 | | 2(2z+1)-6=32 | | (-x-2)*(3x-5)=(-3x+1)*(x+3) | | -3x^2+6=1 | | x(5x-4)(x+9)= | | 7.6x-3.2(3.1x-2.4)= |